Low-Complexity Parallel Min-Sum Medium-Density Parity-Check Decoder for McEliece Cryptosystem - Cai, Jiaxuan; Zhang, Xinmiao (IEEE transactions on circuits and systems. I, Regular papers, 2023)
The McEliece cryptosystem based on medium-density parity-check (MDPC) codes remains a candidate in the fourth round submission of post-quantum cryptography standard. The low-density parity-check (LDPC) decoders used in digital communications have been extensively studied. However, the MDPC codes for the McEliece cryptosystem have much higher column weight and different structure in their parity-check matrices. As a result, simplification techniques for LDPC decoders are not applicable to MDPC decoders. Besides, existing MDPC decoder designs have been focusing on the simplest bit-flipping algorithm, whose performance is inferior compared to that of the Min-sum algorithm. This paper first optimizes the scaled Min-sum algorithm for codes with high column weight to improve the performance with simple scalar multiplications. The overall decoder architecture is re-designed to take into account the sparsity of the parity-check matrix and nontrivial min-sum check node processing. Besides, a flexible message storage scheme is proposed to reduce the worst-case decoding latency of the randomly constructed codes utilized in the McEliece cryptosystem. Then a 2-stage scaling scheme is developed to reduce the long critical path caused by the high column weight and a group size re-balancing scheme is introduced to mitigate the precision loss caused by the 2-stage scaling in parallel decoders. For an example MDPC decoder, the proposed optimized 2-stage scaled Min-sum algorithm leads to orders of magnitude error-correcting performance improvement and 16% higher clock frequency with negligible silicon area overhead compared to unoptimized Min-sum decoders.